Implementasi Kriptografi Vigenere Cipher untuk Keamanan Data Informasi Desa - Erva Irianti; Dewi Fatmarani Surianto; Ainun Zahra Adistia; Muh. Juharman; Jumadil Ahmad Safi’i (Progressive Information, Security, Computer, and Embedded System, 2023)
Data security on village information is a very important issue because it contains a lot of village information data. Important data cannot be denied that data can be edited or changed by unauthorized persons. So the data becomes insecure. Therefore, a technique is needed to secure data, namely using the classic Vigenere cipher cryptography technique, to maintain the security and confidentiality of messages or information so that it cannot be read by anyone, a desktop-based application is designed using the Java programming language which is carried out on the Netbeans IDE software to implementing the vigenere cipher algorithm as a technique for securing village information.